Dinamika Pengembangan Ilmu di UIN Malang dan UIN Yogyakarta - Mohammad Muslih (Universitas Darussalam Gontor, 2019)
This article intends to look at the latest issues of Philosophy of Science related to the ‎issue of scientific integration, especially those that developes in Islamic State University ‎‎(UIN) Malang and Yogyakarta. In some way, the scientific dynamics of UIN are ‎interesting to study regarding UIN’s success that has been done in building a new ‎scientific paradigm accompanying long-period process of institutional development from ‎Institute to University as its most crucial issue. It is understandable that such a ‎development is a very brilliant stage of scientific achievement recorded in history. The ‎scientific dynamics of UIN also continues to be in a spotlight along with the great ‎expectations -and even a concern- of the community. It is on account that in fact, the ‎development of any scientific paradigm connect or impact broadly on religious ‎understanding of general public. If religion (with all its teachings) is understood as being ‎contrary to science all the time, accordingly, it is impossible for science (with all its ‎characteristics and criteria) to meet with religion. Coming through an advanced scientific ‎paradigm, UIN reconstructs both religious and scientific understanding so that they can ‎meet and even negotiate. Moreover, the two Universities have developed new academic ‎traditions as well, characterized by development patterns in the field of research and ‎scientific works of their academic communities.‎